Quantitative 3-D Model of Carbonate Reef and Shoal Facies Based on UAV Oblique Photogrammetry Data: A Case Study of the Jiantanba Outcrop in West Hubei, China - Yin, Senlin; Zhao, Lei; Lin, Yu; Zhu, Baiyu; Zhao, Junwei; Cheng, Leli (Frontiers in Earth Science, 2022)
To resolve the problems that persist due to the application of insufficient data acquisition methods for steep carbonate outcrops, unmanned aerial vehicle (UAV) oblique photogrammetry was used to quantitative assess the Jiantianba outcrop from a global perspective. The data were rapidly and flexibly acquired, processed and interpreted to establish a geological foundation for the outcrop area, and three-dimensional (3-D) geological modelling of a typical outcrop was carried out. The results show that the model of the Jiantianba carbonate outcrop has 3-D coordinates that correspond to oblique image data, allowing for both the accurate location of any point and the measurement of the rock body, and thus providing a foundation for studying the stratigraphic architecture of the outcrop. Through fine-scale geological and statistical analyses of the geological parameters of three geologic sections, a database and model of a typical outcrop were established, including the types, continuity and scale of lithology, as well as different lithological combinations and the geological evolution of the region. Using virtual well location, lithological calibration, baseline stratification, a geological model and database, 3-D stratigraphic and lithological models of a typical outcrop were established via sequential indicator simulation (SIS). Subsequently, these models were combined with the outcrop geometry, and the training images of different microfacies were analysed. Multi-point geostatistical simulations (MPSs) were then used to establish a 3-D geological model of reef–shoal facies that is more in line with our current understanding of the geology of the outcrop area.